2017
DOI: 10.3390/molecules22071160
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Tartary Buckwheat Extracts on Adipogenesis and Inflammatory Response

Abstract: Tartary buckwheat (Fagopyrum tataricum) has been established globally as a nutritionally important food item, particularly owing to high levels of bioactive compounds such as rutin. This study investigated the effect of tartary buckwheat extracts (TBEs) on adipogenesis and inflammatory response in 3T3-L1 cells. TBEs inhibited lipid accumulation, triglyceride content, and glycerol-3-phosphate dehydrogenase (GPDH) activity during adipocyte differentiation of 3T3 L1 cells. The mRNA levels of genes involved in fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…Hypertrophic adipocyte and immune cell interaction have been well proven for the progression of insulin resistance and noninsulin dependent diabetes [32]. The appropriate ratio of omega-6/omega-3 fatty acid is an important health determinant and decreases the inflammatory condition and cardiovascular disease [33,34]. Our present observation confirmed that the chia seed fatty acid ratio suppresses adipocyte lipogenesis and hypertrophy, which favor the suppression of proinflammatory cytokine formation in the adipose tissue.…”
Section: Resultssupporting
confidence: 82%
“…Hypertrophic adipocyte and immune cell interaction have been well proven for the progression of insulin resistance and noninsulin dependent diabetes [32]. The appropriate ratio of omega-6/omega-3 fatty acid is an important health determinant and decreases the inflammatory condition and cardiovascular disease [33,34]. Our present observation confirmed that the chia seed fatty acid ratio suppresses adipocyte lipogenesis and hypertrophy, which favor the suppression of proinflammatory cytokine formation in the adipose tissue.…”
Section: Resultssupporting
confidence: 82%
“…Researchers found that buckwheat extracts may inhibit adipogenesis and inflammatory response during adipocyte differentiation of 3T3-L1 cells. 24 Brazilian red propolis (Apis mellifera), Copaifera oleoresins, flavonoid fraction of bergamot juice (Citrus bergamia), effusanin C (Isodon japonicus), oligomeric proanthocyanidins (Crataegus oxyacantha) are other isolated compounds with anti-inflammatory actions in activated monocytes and macrophages. [25][26][27][28][29] Lupinus angustifolius L. is a legume that contents a high level of plant protein.…”
Section: Discussionmentioning
confidence: 99%
“…The culture of 3T3-L1 cells was performed as described previously [ 37 ]. Mouse 3T3-L1 preadipocytes were maintained in DMEM containing 10% ( v / v ) BCS, 100 units/mL penicillin, 100 μg/mL streptomycin, and 2 mM glutamine under conditions of 37 °C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxicity of ISOR in adipocytes was evaluated using the WST-8 [2-(2-methoxy-4-nitropheyl)-3-(4-nitrophenyl)-5-(2,4-dinitrophenyl)-2H-tetrazolium, monosodium salt method, with a commercial CCK-8 kit as described previously [ 37 ]. Differentiated 3T3-L1 adipocytes were incubated for 1, 2, 5, or 7 days with ISOR (at a dose of 0, 0.1, 0.5, 1, 10, 20, or 50 µM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation